2020
DOI: 10.3390/ma13204680
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Milling Accuracy of Zirconia-Reinforced Lithium Silicate Crowns Fabricated Using the Dental Medical Device System: A Three-Dimensional Analysis

Abstract: This study aimed to analyze the milling accuracy of lithium disilicate and zirconia-reinforced silicate crown fabricated using chairside computer-aided design/manufacturing (CAD/CAM) system. Mandibular left first premolar was selected for abutment. A master model was obtained for digital impression using an intraoral scanner, and crowns were designed using a CAD software design program. Amber Mill (AM), IPS e max CAD (IPS), and CELTRA DUO (CEL) were used in the CAD/CAM system, and a total 45 crowns (15 crowns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Previous studies have investigated NLD’s different mechanical properties [ 7 , 17 , 18 , 20 ]. Yin et al [ 20 ] have reported that NLD had higher Vickers hardness and biaxial flexural strength values, along with a more stable surface topography than CAD-CAM composite blocks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have investigated NLD’s different mechanical properties [ 7 , 17 , 18 , 20 ]. Yin et al [ 20 ] have reported that NLD had higher Vickers hardness and biaxial flexural strength values, along with a more stable surface topography than CAD-CAM composite blocks.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has investigated the fracture toughness of lithium silicate ceramics and concluded that NLD had higher values than ZLS [ 7 ]. Kang et al [ 18 ] showed that NLD and LDS have similar milling accuracy that was higher than that of ZLS. Considering the results of the present and those previous studies on NLD, it can be speculated that NLD might be a favorable material mechanically, but this hypothesis should be substantiated with future in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, for zirconia manufactured with the AM technology to be used in dental practice, the zirconia-based dental prosthesis must have micro-level accuracy to ensure a perfect fit with the abutment and prevent secondary caries in the oral cavity. Several studies have evaluated the accuracy of zirconia dental prostheses manufactured with SM technology [ 22 , 23 , 24 ]. Most of these studies have focused on the internal and marginal fitting accuracy between the abutment and crown prepared by SM technology, and the fitting accuracy was better than those of the dental prostheses manufactured via conventional dental technology; however, few studies have focused on the manufacturing accuracy of zirconia dental prostheses based on AM technology.…”
Section: Introductionmentioning
confidence: 99%